METHODS OF PREPARING AND ORGANIZING FAMILY OF NURSERY BEES - Jamolov R. Q.; Sharofiddinova G.H. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: in the article, the breeder should prepare in advance for the organization of bee families and receive the larvae for education, in such families there should be up to 2-2.5 kg of bees, they are physiologically sufficient - age, mammary glands and wax production. excretory glands should be developed. In addition, there should always be 6-7 kg of feed honey and 2-3 frames of pollen in the breeding bee families, in order to raise queen bees in early spring, in order to strengthen such breeding families, they should be given from closed breeding frames, as well as stimulating juice. Conclusions are given about the expediency of feeding, shortening the nest and keeping it warm.